2011
DOI: 10.1111/j.1574-6968.2011.02402.x
|View full text |Cite
|
Sign up to set email alerts
|

Passage through Tetrahymena tropicalis enhances the resistance to stress and the infectivity of Legionella pneumophila

Abstract: Legionella pneumophila is a gram-negative bacterium prevalent in fresh water which accidentally infects humans and is responsible for the disease called legionellosis. Intracellular growth of L. pneumophila in Tetrahymena is inconsistent; in the species Tetrahymena tropicalis stationary-phase forms (SPFs) of L. pneumophila differentiate into mature intracellular forms (MIFs) without apparent bacterial replication and are expelled from the ciliate as pellets containing numerous MIFS. In the present work, we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 20 publications
(42 reference statements)
0
36
1
Order By: Relevance
“…Increased resistance to antibiotics was also described after incubation of L. pneumophila in Acanthamoeba castellanii buffer for 16 h (12). MIFs are able to resist starvation better than stationary-phase forms in encystment buffer (11), but both forms show similar levels of resistance in distilled water (8).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Increased resistance to antibiotics was also described after incubation of L. pneumophila in Acanthamoeba castellanii buffer for 16 h (12). MIFs are able to resist starvation better than stationary-phase forms in encystment buffer (11), but both forms show similar levels of resistance in distilled water (8).…”
mentioning
confidence: 96%
“…Infection of HeLa cells and Tetrahymena tropicalis leads to the differentiation of L. pneumophila into mature infectious forms (MIFs), characterized by ultrastructural changes and accumulation of poly-␤-hydroxybutyrate (8)(9)(10). MIFs are highly infectious and are more resistant to antibiotics and detergent than other forms (9,11). Increased resistance to antibiotics was also described after incubation of L. pneumophila in Acanthamoeba castellanii buffer for 16 h (12).…”
mentioning
confidence: 98%
“…was reported for E. coli O157:H7 (44,45), L. pneumophila (35), S. enterica (33,46), and E. coli K-12 (47). A few dead cells were observed after 24 h of coincubation (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Bacteria packaged and excreted in MLBs have greater resistance to unfavorable conditions (32)(33)(34). For example, it was shown that L. pneumophila packaged in MLBs by the ciliate Tetrahymena tropicalis was more infectious and displayed greater resistance to gentamicin and longer survival in a nutrient-poor environment, compared to the planktonic state (35).…”
mentioning
confidence: 99%
“…This is why Tetrahymena infection is very dangerous to many fish species [69]. However, not only fishes but also mammals, including human, are touched by different infections, as by a similar way, the L. pneumophila [70,71] and Salmonella enterica [72], causing diseases, are transported. In addition, in some cases, the microbes during their stay in the phagocytic vesicles can be transformed to more pathogenic 284 CSABA and hypervirulent forms [73].…”
Section: Discussionmentioning
confidence: 99%